The Comparison of the Material Properties of Reverse Osmosis Membranes with Respect to Their Performances - Suryo Gandasasmita (Jurnal Matematika & Sains, 1998)
Reverse osmosis has been used for water desalination. The performance of a reverse osmosis membranes is very much determined by both the natural properties of polymeric membrane materials, as well as the properties created through the manufacturing process. The purpose of this research is to study the influence of membrane material properties on the membrane performance in relation to its flux and solute rejection in reverse osmosis process. In this study, three membranes were prepared for reverse osmosis application, namely polysulfon membrane (PSf) and cellulose acetate membranes (CA27 and CA05). The CA05 membrane had the best performance among the three membranes, with reasonable flux and moderate rejection. Upon the examination of the three membranes, the differences of the membrane material properties became clear. Each property works in synergy to optimize membrane performance.